Permasalahan Terkait Kuantitas Regulasi Dalam Penyelesaian Sengketa Tata Usaha Negara - Diani Kesuma (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
It is often encountered basic orderly of laws and regulations problematic, which areuncontrollable types of regulations which could be classified as laws and regulations which aresometimes contained materials the one who resist the higher laws and regulations. Theexistence of Article 8 Paragraph (1) of Law Number 12 Year 2011Concerning Formation ofLaw and Regulations often is interpreted all regulations such as People’s Advisory Councilregulation, The House of Representative regulations, Regional Representative Councilregulation, Supreme Court regulation, Constitutional Court regulation are categorized as lawsand regulation as long as ordered by the higher regulation or established by authority. In fact,not all of those institutions could produce laws and regulations which binds externally. Tocreate basic orderly and formatting laws and regulations need re arrangement among others tothe types, hierarchy, and material content of laws and regulations. The existence of JobCreation Law does not a way out to solve the problem related to quantity of regulations. Article175 of Law Number 11 Year 2020 Concerning Job Creation Cluster GovernmentAdministration does not codify all related regulations with litigation process in stateAdministration Court, due to the litigation process still refer to the previous law. Expected theprovision of litigation process which are governed in various Law and Supreme Court Regulation could be arranged with unify to one law, to make easier for the justice seeker whichinvolved in State Administration disputeprovision of litigation process which are governed in various Law and Supreme Court